Wonderful worms : a 4D book - Peterson, Megan Cooley (Pebble, 2020)
"Dig in the dirt and you'll find . . . worms! But did you know that many live underwater? Or that some can grow as long as 9 feet? Excite kids' natural curiosity with this Smithsonian Little Entomologist book about wonderful worms from around the world. Readers will be wowed by the amazing variety of wrigglers and up-close photos, while also learning about bug behavior, life cycles, classification, and more. The engaging, leveled text supports life science curriculum"--
Make way for worms -- Earthworms -- Leeches -- Bristle worms -- Roundworms -- Tapeworms -- Flukes -- Marine flatworms -- Ribbon worms.
"Little Explorer is published by Pebble."
Includes bibliographical references and index.
Ages 4-8.
Grades K-1.
Keywords: Worms -- Juvenile literature